Tumor Response Criteria in Oncoimaging: RECIST Criteria and beyond—Part 2 - Baheti, Akshay D.; Rastogi, Ashita; Natarajan, Aravintho; Patra, Anurima; Tirumani, Sree Harsha (Journal of Gastrointestinal and Abdominal Radiology, 2019)
The rapid recent advances in oncology have made the dream of precision oncology a reality, with targeted therapy available for various tumors depending on the molecular genotype. This has led to the corresponding development of personalized radiology as well, with various tumor response criteria used to characterize disease response/progression depending on chemotherapy used. In these two review articles, we review the various tumor response criteria widely applied in both research and clinical settings. These include the classic size-based criteria such as RECIST (Response Evaluation Criteria In Solid Tumors) 1.1 and the WHO (World Health Organization) criteria, as also various other criteria such as Choi and modified Choi criteria for tumors treated by targeted therapy, EASL (European Association for the Study of the Liver) and modified RECIST (mRECIST) criteria for hepatocellular carcinomas, immune-related response criteria (irRC) and immune RECIST (iRECIST) for patients on immunotherapy. Other clinically important criteria such as PERCIST (PET Response Criteria In Solid Tumors) for positron emission tomography–computed tomography (PET-CT), and the MD Anderson criteria for evaluating bone metastases are also highlighted.
Keywords: treatment response; modified RECIST; Choi criteria; MD Anderson criteria; PERCIST; immune RECIST